Cefdinir and β-Lactamase Inhibitor Independent Efficacy Against Mycobacterium tuberculosis - Shashikant Srivastava; Shashikant Srivastava; Tania Thomas; Dave Howe; Lesibana Malinga; Prithvi Raj; Jan-Willem Alffenaar; Jan-Willem Alffenaar; Jan-Willem Alffenaar; Tawanda Gumbo; Tawanda Gumbo (Frontiers Media S.A., 2021)
Background: There is renewed interest in repurposing β-lactam antibiotics for treatment of tuberculosis (TB). We investigated efficacy of cefdinir, that withstand the β-lactamase enzyme present in many bacteria, against drug-susceptible and multi-drug resistant (MDR) Mycobacterium tuberculosis (Mtb).Methods: Minimum inhibitory concentration (MIC) experiments were performed with Mtb H37Ra, eight drug-susceptible, and 12 MDR-TB clinical isolates with and without the β-lactamase inhibitor, avibactam at 15 mg/L final concentration. Next, we performed dose-response study with Mtb H37Ra in test-tubes followed by a sterilizing activity study in the pre-clinical hollow fiber model of tuberculosis (HFS-TB) study using an MDR-TB clinical strain. Inhibitory sigmoid Emax model was used to describe the relationship between the drug exposure and bacterial burden.Results: Cefdinir MIC for Mtb H37Ra was 4 and 2 mg/L with or without avibactam, respectively. The MIC of the clinical strains ranged between 0.5 and 16 mg/L. In the test-tube experiments, cefdinir killed 4.93 + 0.07 log10 CFU/ml Mtb H37Ra in 7 days. In the HFS-TB studies, cefdinir showed dose-dependent killing of MDR-TB, without combination of avibactam. The cefdinir PK/PD index linked to the Mtb sterilizing efficacy was identified as the ratio of area under the concentration-time curve to MIC (AUC0-24/MIC) and optimal exposure was calculated as AUC0-24/MIC of 578.86. There was no resistance emergence to cefdinir in the HFS-TB.Conclusion: In the HFS-TB model, cefdinir showed efficacy against both drug susceptible and MDR-TB without combination of β-lactamase inhibitor. However, clinical validation of these findings remains to be determined.